The Effectiveness of Mathematics Worsheet Based on Creative Problem Solving (CPS) for Reasoning Ability of Elementary School Students - Jusmawati, Jusmawati; Satriawati, Satriawati; Rahim, Irman; Rahman, Abdul; Arsyad, Nurdin (Universitas Negeri Makassar, 2021)
This study aimed to know the effectiveness of creative problem solving (CPS) based mathematics worksheet reviewed by reasoning ability of students’ elementary school. This study used experimental method with Randomized Subject Posttest Only Control Group Design. The samples of this study consisted of two classes namely experimental class (Creative Problem Solving based Mathematics Worksheet) and control class ( conventional method). The taking of sample was conducted by cluster random sampling. Technique of data collecting consisted of cognitive aspect using objective test method and affective aspect using questionnaire. Technique of data analysis applied descriptive and inferential analysis. The hypothesis test used t-test by requirement of normality test and homogeny. The result of study indicated that (1) learning by using creative problem solving (CPS) based mathematics worksheet was implemented well. (2) The implementation of creative problem solving (CPS) based mathematics worksheet was reviewed by aspects: (a) mean score of students’ reasoning was 87,12 categorized as a very good. The gain was 0,78. The students’ reasoning ability classically was 91,25% ≥85%. (b) students’ learning activity was categorized as a good. (c) responds were categorized as a positive. The result of hypothesis test on 0,05 significant using t-test indicated that learning of creative problem solving (CPS) based mathematics worksheet was effective to students’ reasoning of elementary school.